In-vitro Activity of Isepamicin against Gram-negative Bacteria in Comparison to Other Aminoglycosides Routinely used at a Teaching Hospital in Northern India - Siddiqui, Tasneem; Kar, Mitra; Dubey, Akanksha; Patel, Sangram Singh; Sahu, Chinmoy (Journal of Laboratory Physicians, 2023)
Background Isepamicin is a 1-N-S-a-hydroxy-b-aminopropionyl derivative of gentamicin B and the spectrum of pathogenic microorganisms covered by it and its effectiveness is similar to that of amikacin except the action of aminoglycoside inhibitor enzymes is ineffectual on it.Material and Methods We performed a prospective study in the Bacteriology section of the Department of Microbiology at a 1,600-bedded hospital in Northern India from Jan 2022 to March 2022. Isepamicin was tested for susceptibility against gram-negative bacteria, identified by routine biochemicals and matrix-assisted-desorption/ionization –time of flight-mass spectrometry (MALDI-TOF-MS) assay. The antibiotic susceptibility testing for each of the isolates was performed by Kirby Bauer's disc diffusion method, according to the CLSI 2019 guidelines.Results The majority of isolates were obtained from blood samples (50, 39.1%). Among the non-inducible Enterobacteriaceae, Escherichia coli was least susceptible to amikacin (8/27, 29.63%) and most susceptible to isepamicin (18/27, 66.67%). Klebsiella pneumoniae followed the same pattern of susceptibility as E. coli and was least susceptible to Amikacin (20/46, 43.48%) and most susceptible to isepamicin (24/46, 52.17%). Enterobacter cloacae (6/7, 85.71%) was most susceptible to both amikacin and isepamicin, followed by 71.43% (5/7, 71.43%) susceptibility to gentamicin and tobramycin each. Enterobacter aerogenes was equally 53.33% (8/15) susceptible to all antibiotics. Pseudomonas aeruginosa was the most susceptible isolate to all antibiotics (18/21, 85.71%).Conclusion Isepamicin is a potential antimicrobial agent for treating an array of gram-negative bacteria-associated infections and shows better in vitro activity than older aminoglycoside agents.
Keywords: isepamicin; MALDI-TOF-MS; gram-negative bacteria; gentamicin B; antimicrobial agents